2011
DOI: 10.1016/j.bmc.2011.08.054
|View full text |Cite
|
Sign up to set email alerts
|

Potent inhibition of Norwalk virus by cyclic sulfamide derivatives

Abstract: A new class of compounds that exhibit anti-norovirus activity in a cell-based system and embody in their structure a cyclosulfamide scaffold has been identified. The structure of the initial hit (compound 2a, ED50 4 μM, TD50 50 μM) has been prospected by exploiting multiple points of diversity and generating appropriate structure-activity relationships.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 16 publications
(20 reference statements)
0
24
0
Order By: Relevance
“…In the case of inhibitors incorporating an aldehyde or α-ketoamide functionality in their structure, interaction with the active site cysteine (Cys139) leads to the formation of a reversible adduct (Figure 2). 17a–c …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of inhibitors incorporating an aldehyde or α-ketoamide functionality in their structure, interaction with the active site cysteine (Cys139) leads to the formation of a reversible adduct (Figure 2). 17a–c …”
Section: Resultsmentioning
confidence: 99%
“…1516 Cleavage is at the P 1 -P 1 ’ (Q–G) scissile bond. We have recently reported an array of norovirus inhibitors, including acyclic and cyclic sulfamide 1719 and piperazine 20 derivatives. We have also disclosed for the first time peptidyl transition state (TS) inhibitors, 13a–e TS mimics, 13f as well as macrocyclic inhibitors 13g effective in enzyme and cell based assays.…”
Section: Introductionmentioning
confidence: 99%
“…These include cyclic and acyclic sulfamides [9091] and structural variants [9294], pyranobenzopyrones [95], and chromones [96] (Figure 9). …”
Section: Drugs Against Known Targetsmentioning
confidence: 99%
“…We have recently reported that cyclosulfamide-based derivatives potently inhibit norovirus replication in a cell-based system [4] and have, furthermore, used a scaffold hopping strategy to identify additional classes of compounds that inhibit noroviruses [5]. The multiple points of diversity present in structure (I) (Figure 1) were used to carry out structural modifications to prospect the entire structure and to obtain preliminary validation for advancing this series of compounds into the lead optimization phase [6].…”
Section: Introductionmentioning
confidence: 99%